Dissociated late potentials during sinus rhythm after radiofrequency ablation in a patient with postinfarction ventricular tachycardia. Issue 4 (13th November 2013) - Nakahara, Shiro; Hori, Yuichi; Kobayashi, Sayuki; Tsukada, Naofumi; Sakai, Yoshihiko; Takayanagi, Kan
Abstract: A 72‐year‐old man with ischemic cardiomyopathy was admitted for the treatment of ventricular tachycardia (VT). Because his VT was poorly tolerated hemodynamically, substrate mapping was performed. The map revealed the presence of low‐voltage areas in the inferolateral wall of the LV. Late potentials (LPs) were recorded during sinus rhythm, and pacing at the site revealed a good pacemap for targeting the VT. Delivery of radiofrequency (RF) current to the area where LPs were recorded rendered the targeted VT noninducible. After RF delivery, dissociation of the LPs with an interval of 3140 ms was documented during sinus rhythm.